Measurements of Basic Performances for Waterjet Propulsion Systems in Water Tunnel - Nobuyuki Fujisawa (International Journal of Rotating Machinery)
Experimental techniques are described in detail for evaluating the system and the unit performances of waterjet propulsion systems in a water tunnel. The measured performances of pump and propulsion of the model systems are in reasonable agreement with the field experiment with prototype craft. Measurements are also made for the losses in the intake and the nozzle. The optimization study of the water jet systems is conducted by simulating the change of the nozzle outlet diameter with the variable nozzle arrangement. It is suggested that the nozzle outlet diameter should be decreased as the craft velocity increases to obtain an optimum propulsive efficiency in a wide range of craft velocity.